Climate and industrial policy in an asymmetric world - Thomas Gries (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Climate change is a phenomenon leading to randomly distributed disasters around the globe. Due to massive economic and technical asymmetry between the advanced North and the developing South efficient climate and industrial policy is particular difficult. Globally efficient policy would need to equip the South with pollution reducing technologies. However, there is a tradeoff between capital accumulation for consumption growth and low-carbon development. The pollution stock affecting today's climate was historically accumulated by the North, therefore, the 'ability-to-pay principal' and the 'polluter pays principle' suggest to allocate the main burden of climate change policy to the advanced economies.
Keywords: Q54; Q25; Q14; 330; climate change policy; North-South asymmetries; stock pollution; distribution of burdens; Klimaveränderung; Industriepolitik; Süd-Nord-Gefälle